Nature of Tasks when Teaching French with the Café Crème Textbook - Bírová, Jana; Klinka, Tomáš (Journal of Education Culture and Society, 2025)
Aim. The aim of the research was to find out the balance between the typology of the exercises and activities within the textbook Café-Crème. Methods. We used the structural-tasks analysis, the theory of communicative curve and Markov chain statistical method. Results. The textbook sequence reveals how tasks progress through different levels of communication potential, from grammar-focused exercises (State 1) to more contextual and communicative tasks (States 4, 6, and 7). The transitions provide insight into the textbook’s structure and its approach to developing communication skills. Student’s Book Focus (First Dataset) offers a more balanced mix, with greater emphasis on contextual tasks (State 4) and pragmatic activities (State 6). It also incorporates more open communicative tasks (State 7), though these often revert to grammar-focused tasks. Exercise Book (Second Dataset) primarily emphasizes repetitive grammar-focused tasks (State 1), with limited but targeted transitions to higher-order tasks (States 4, 6, and 7). This book serves as a foundation, consolidating basic skills. Conclusions. The exercise book lays a solid foundation for grammar and basic language structures (State 1), but it offers minimal direct pathways to higher-order communicative activities (States 4, 6, and 7). The student’s book complements this with more balanced task types, including contextual, pragmatic, and communicative tasks, though transitions could be improved. While the student’s book attempts to bridge foundational tasks and communicative tasks, the transitions to State 7 (open communication) remain weak across both books. This indicates a need for more explicit scaffolding towards real-world communication. Both components of the book show significant clustering within each task type (e.g., repeating grammar exercises in State 1 or grouping receptive tasks in State 4). While this reinforces specific skills, it risks reducing variety and engagement.